PENGGUNAAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS V SD NEGERI 05 BANDAR BUAT KOTA PADANG - Stefani Stefani; Zainal Abidin (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to describe the use of the Problem Based Learning model to improvement of student learning outcomes in integrated thematic learning in the fifth grade of SD N 05 Bandar BuatPadang. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection. The subjects of this study were researchers, teachers, and fifth grade students of SD N 05 Bandar BuatPadang, totaling 27 people. The results of the study in the first cycle of learning outcomes reached a percentage of completeness of 25% (Less category) with an average value of 3.12 (good category) increased in the second cycle percentage of completeness 90% (very good category) with an average achievement of 3.75 (very good category).Keywords: Problem Based Learning, Integrated Thematic Learning.